Pengelolaan Aset Tanah Dan Bangunan Pemerintah Daerah Kabupaten Gorontalo - Udin Pango (CV. Dalle’ Deceng Abeeayla, 2024)
This research aims to describe and understand the management of Gorontalo Regency Regional Government Land and Building Assets in terms of their use and formulate strategies that can be implemented to optimize regional asset management in Gorontalo Regency. This research was conducted using a descriptive qualitative approach with data collection techniques through observation, in-depth interviews and documentation. Based on the research results obtained, in general the management of regional property in the Gorontalo Regency Government through regional asset utilization activities has been carried out well, but there are still no certain parties, both private and private, in the form of leasing and borrowing for other forms. The BUMN/BUMD that were involved, apart from that, still found building land assets that had not been utilized, had not been certified and were in dispute. Strategic steps that can be taken by Regional Governments to Effectively Utilize Regional Assets are by carrying out inventory of goods and legal audits of regional asset utilization; creating a regional asset utilization system based on information technology (SIMA); carry out structural renewal and asset restructuring”. Suggestions or recommendations that can be put forward as a result of this research are to change the regional asset management paradigm by making assets one of the potential regional original income through joint activities involving all stakeholders (regional government, private sector and community).